Marginal deterioration of the silicone for facial prosthesis with pigments after effect of storage period and chemical disinfection - Guiotti, Aimée Maria; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos (Wolters Kluwer, 2010)
The failure of facial prostheses is caused by limitations in the properties of existing materials, especially flexibility and durability. Therefore, this study evaluated the marginal deterioration of a silicone used for fabrication of facial prostheses (Silastic MDX4-4210, Dow Corning Corporation, Midland, MI, USA) according to the influence of artificial aging, daily disinfection, and 2 types of pigmentation. Thirty specimens were fabricated and subdivided in 6 groups: without pigmentation, pigmented with make-up powder and iron oxide, and evaluated with and without the action of the disinfectant. Analysis of marginal deterioration was performed on a scanning electron microscope (magnification, ×5000) immediately 6 months and 1 year after fabrication of specimens, following the guidelines of ASTM International. After visual analysis of the photomicrographs, it was noticed that all groups presented marginal deterioration and alterations in surface texture with time. The use of disinfection did not contribute to the marginal deterioration of polymer (silicone), regardless of the pigmentation and artificial aging.
Keywords: Maxillofacial prostheses